Large‐Scale Characterization of Systemic Sclerosis Serum Protein Profile: Comparison to Peripheral Blood Cell Transcriptome and Correlations With Skin/Lung Fibrosis. Issue 4 (28th February 2021) - Bellocchi, Chiara; Ying, Jun; Goldmuntz, Ellen A.; Keyes‐Elstein, Lynette; Varga, John; Hinchcliff, Monique E.; Lyons, Marka A.; McSweeney, Peter; Furst, Daniel E.; Nash, Richard; Crofford, Leslie J.; Welch, Beverly; et al.
Abstract : Objective: To provide a large‐scale assessment of serum protein dysregulation in diffuse cutaneous systemic sclerosis (dcSSc) and to investigate serum protein correlates of SSc fibrotic features. Methods: We investigated serum protein profiles of 66 participants with dcSSc at baseline who were enrolled in the Scleroderma: Cyclophosphamide or Transplant Trial and 66 age‐ and sex‐matched healthy control subjects. A panel of 230 proteins, including several cytokines and chemokines, was investigated. Whole blood gene expression profiling in concomitantly collected samples was performed. Results: Among the participants with dcSSc, the mean disease duration was 2.3 years. All had interstitial lung disease (ILD), and none were being treated with immunosuppressive agents at baseline. Ninety proteins were differentially expressed in participants with dcSSc compared to healthy control subjects. Similar to previous global skin transcript results, hepatic fibrosis, granulocyte and agranulocyte adhesion, and diapedesis were the top overrepresented pathways. Eighteen proteins correlated with the modified Rodnan skin thickness score (MRSS). Soluble epidermal growth factor receptor was significantly down‐regulated in dcSSc and showed the strongest negative correlation with the MRSS, being predictive of the score's course over time, whereas α1 ‐antichymotrypsin was significantly up‐regulated in dcSSc and showed the strongest positive correlation with the MRSS. Furthermore, higher levels of cancer antigen 15‐3 correlated with more severe ILD, based on findings of reduced forced vital capacity and higher scores of disease activity on high‐resolution computed tomography. Only 14 genes showed significant differential expression in the same direction in serum protein and whole blood RNA gene expression analyses. Conclusion: Diffuse cutaneous SSc has a distinct serum protein profile with prominent dysregulation of proteins related to fibrosis and immune cell adhesion/diapedesis. The differential expression for most serum proteins in SSc is likely to originate outside the peripheral blood cells.